Alchemilla vulgaris modulates isoproterenol-induced cardiotoxicity: interplay of oxidative stress, inflammation, autophagy, and apoptosis - Anajirih, Nuha; Abdeen, Ahmed; Taher, Ehab S.; Abdelkader, Afaf; Abd-Ellatieff, Hoda A.; Gewaily, Mahmoud S.; Ahmed, Nashwa E.; Al-Serwi, Rasha H.; Sorour, Safwa M.; Abdelkareem, Heba M.; Ebrahim, Elturabi; El-Sherbiny, Mohamed; et al. (Frontiers in Pharmacology, 2024)
Isoproterenol (ISO) is regarded as an adrenergic non-selective β agonist. It regulates myocardial contractility and may cause damage to cardiac tissues. Alchemilla vulgaris (AV) is an herbal plant that has garnered considerable attention due to its anti-inflammatory and antioxidant bioactive components.The present investigation assessed the cardioprotective potential of AV towards ISO-induced myocardial damage. Four groups of mice were utilized: control that received saline, an ISO group (85 mg/kg, S.C.), ISO+AV100, and ISO+AV200 groups (mice received 100 or 200 mg/kg AV orally along with ISO). ISO induced notable cardiac damage demonstrated by clear histopathological disruption and alterations in biochemical parameters. Intriguingly, AV treatment mitigates ISO provoked oxidative stress elucidated by a substantial enhancement in superoxide dismutase (SOD) and catalase (CAT) activities and reduced glutathione (GSH) content, as well as a considerable reduction in malondialdehyde (MDA) concentrations. In addition, notable down-regulation of inflammatory biomarkers (IL-1β, TNF-α, and RAGE) and the NF-κB/p65 pathway was observed in ISO-exposed animals following AV treatment. Furthermore, the pro-apoptotic marker Bax was downregulated together with autophagy markers Beclin1 and LC3 with in ISO-exposed animals when treated with AV. Pre-treatment with AV significantly alleviated ISO-induced cardiac damage in a dose related manner, possibly due to their antioxidant and anti-inflammatory properties. Interestingly, when AV was given at higher doses, a remarkable restoration of ISO-induced cardiac injury was revealed. Table 1. Molecular docking interaction of Alchemilla vulgaris's bioactive compounds against TNF-α, IL-1β, NF-κB1, Bax, RAGE, and HMBG1 Ligands Binding Free Energy (kcal/mol) TNF-α IL-1β NF-κB1 Bax RAGE HMBG1